Didactic Opportunities of the Educational Cluster in Increasing the Efficiency of Inclusive Education - Matupaeva Shohsanam (Researchparks Publishing, 2022)
The article describes the didactic possibilities of the educational cluster in increasing the effectiveness of inclusive education. The technologies designed to ensure the readiness of pedagogues for inclusive education in the conditions of an educational cluster ensure the gradual acquisition, differentiation, integration and individualization of pedagogues' experience in inclusive education. Based on the prediction based on androgogical-diagnostics about the readiness of teachers for inclusive education, we studied systematic, person-oriented, activity, axiological, competence approaches.